Probing the Shock Breakout Signal of SN 2024ggi from the Transformation of Early Flash Spectroscopy - Zhang, Jujia; Dessart, Luc; Wang, Xiaofeng; Zhai, Qian; Yang, Yi; Li, Liping; Lin, Han; Valerin, Giorgio; Cai, Yongzhi; Guo, Zhen; Wang, Lingzhi; Zhao, Zeyi; et al. (Astrophysical journal. Letters, 2024)
We present early-time, hour-to-day cadence spectroscopy of the nearby Type II supernova (SN II) 2024ggi, which was discovered at a phase when the SN shock had just emerged from the red supergiant (RSG) progenitor star. Over the first few days after the first light, SN 2024ggi exhibited prominent narrow emission lines formed through intense and persistent photoionization of the nearby circumstellar material (CSM). In the first 63 hr, spectral lines of He, C, N, and O revealed a rapid rise in ionization as a result of the progressive sweeping up of the CSM by the shock. The duration of the IIn-like spectra indicates a dense and relatively confined CSM distribution extending up to ∼4 × 10 14 cm. Spectral modeling reveals that a CSM mass-loss rate at this region exceeding 5 × 10 −3 M ⊙ yr −1 is required to reproduce low-ionization emissions, which dramatically exceeds that of an RSG. Analyzing the H α emission shift implies the velocity of the unshocked outer CSM to be between 20 and 40 km s −1 , matching the typical wind velocity of an RSG. The differences between the inner and outer layers of the CSM and an RSG progenitor highlight a complex mass-loss history before the explosion of SN 2024ggi.